2011
DOI: 10.1128/iai.05493-11
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Produce Interleukin 17A (IL-17A) in a Dectin-1- and IL-23-Dependent Manner during Invasive Fungal Infection

Abstract: We have previously reported that compromised interleukin 17A (IL-17A) production in the lungs increased susceptibility to infection with the invasive fungal pathogenAspergillus fumigatus. Here we have shown that culturing lung cells fromA. fumigatus-challenged miceex vivodemonstrated Dectin-1-dependent IL-17A production. In this system, neutralization of IL-23 but not IL-6, IL-1β, or IL-18 resulted in attenuated IL-17A production.Il23mRNA expression was found to be lower in lung cells fromA. fumigatus-challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
142
5
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(160 citation statements)
references
References 45 publications
(47 reference statements)
8
142
5
2
Order By: Relevance
“…93 Similarly, in an experimental model of pulmonary A. fumigatus colonization in immunocompetent mice, clearance of the fungus from the airways was associated with the development of Th17 responses, 145 and IL-17 production by neutrophils has been found to be protective in a model of A. fumigatus keratitis. 144 Similar conflicting results have been reported from human studies. A. fumigatus was a weak inducer of IL-17 production in human T-cells in vitro, and low levels of IL-17 were detected in the bronchoalveolar lavage (BAL) of patients with IA.…”
Section: The Adaptive Immune Response To Aspergillosis In Hsct Patientscontrasting
confidence: 47%
See 1 more Smart Citation
“…93 Similarly, in an experimental model of pulmonary A. fumigatus colonization in immunocompetent mice, clearance of the fungus from the airways was associated with the development of Th17 responses, 145 and IL-17 production by neutrophils has been found to be protective in a model of A. fumigatus keratitis. 144 Similar conflicting results have been reported from human studies. A. fumigatus was a weak inducer of IL-17 production in human T-cells in vitro, and low levels of IL-17 were detected in the bronchoalveolar lavage (BAL) of patients with IA.…”
Section: The Adaptive Immune Response To Aspergillosis In Hsct Patientscontrasting
confidence: 47%
“…3,143 An initial study reported that neutralization of IL-17 and IL-23 in immunocompetent mice improved the outcome of IA and suggested that the IL-23/IL-17 axis inhibits protective Th1 mediated responses while inducing damaging host inflammatory responses. 144 However, other studies using anti-IL-17 antibodies have reported that neutralization of IL-17A renders mice more susceptible to A. fumigatus infection. 93 Similarly, in an experimental model of pulmonary A. fumigatus colonization in immunocompetent mice, clearance of the fungus from the airways was associated with the development of Th17 responses, 145 and IL-17 production by neutrophils has been found to be protective in a model of A. fumigatus keratitis.…”
Section: The Adaptive Immune Response To Aspergillosis In Hsct Patientsmentioning
confidence: 98%
“…Depleting either CD4 + T cells or neutrophils singly in gal3 +/+ mice significantly reduced the IL-17A level (Fig. 4C), indicating that resembling infection by Aspergillus fumigatus, neutrophils, in addition to CD4 + T cells, contribute to IL-17A production in histoplasmosis (44). Interestingly, depleting neutrophils singly completely abolished IL-17A production.…”
Section: Discussionmentioning
confidence: 87%
“…4E). Comparing neutrophils purified from A. fumigatus-infected dectin-1 2/2 mice with cells from infected dectin-1 +/+ mice, Werner et al (44) reported that, although Rorc (Rorgt) mRNA is significantly higher in the former than in the latter, IL-17A production is incoordinately lower in the former. It appears that, unlike in Th17 cells, IL-17A expression in neutrophils in response to IL-23 stimulation is not under the transcription regulation of RORgt.…”
Section: Discussionmentioning
confidence: 99%
“…The production of both is influenced by dectin-1. In candidiasis, the mechanisms by which dectin-1 regulates IL-17A/IL-17F production and in which innate immune cells this occurs is not known, but it is of interest that both neutrophils 37 and c-dT cells 38 produce IL-17A via dectin-1. Altogether, our data indicate that the net activity of dectin-1 in antifungal mucosal immunity is dependent on the host's genetic background and affects both the innate production of IL-17A, IL-17F and IL-22 and the regulation of the Th1/Th17/Treg balance in adaptive immunity.…”
mentioning
confidence: 99%